Bacteriophages Infecting Gram-Negative Bacteria in a Commercial Cucumber Fermentation - Lu, Zhongjing; Pérez-Díaz, Ilenys M.; Hayes, Janet S.; Breidt, Fred (Frontiers in Microbiology, 2020)
Cucumber fermentations are one of the most important vegetable fermentations in the United States. The fermentation is usually driven by lactic acid bacteria (LAB) indigenous to fresh cucumbers. But LAB on fresh cucumbers are greatly outnumbered by many Gram-negative bacteria which may influence the growth of LAB and also cause bloater defect (gas pockets formed in fermented cucumbers) leading to serious economic loss to the pickle industry. Rapid elimination of Gram-negative bacteria is crucial to the dominance of LAB and the reduction of bloater defect in the fermentation. Various factors can affect the viability of Gram-negative bacteria in cucumber fermentation. Bacteriophages (phages) may be one of such factors. This study explored the abundance, diversity, and functional role of phages infecting Gram-negative bacteria in a commercial cucumber fermentation. Cover brine samples were taken from a commercial fermentation tank over a 30-day period. On day 1 and day 3 of the fermentation, 39 Gram-negative bacteria and 26 independent phages were isolated. Nearly 67% of Gram-negative bacterial isolates were susceptible to phage infection. Phage hosts include Enterobacter, Citrobacter, Escherichia, Pantoea, Serratia, Leclercia, Providencia, and Pseudomonas species. About 88% of isolated phages infected the members in the family Enterobacteriaceae and 62% of phages infected Enterobacter species. Eight phages with unique host ranges were characterized. These phages belong to the Myoviridae, Siphoviridae, or Podoviridae family and showed distinct protein profiles and DNA fingerprints. The infectivity of a phage against Enterobacter cloacae was evaluated in cucumber juice as a model system. The phage infection at the multiplicity of infection 1 or 100 resulted in a 5-log reduction in cell concentration within 3 h and rapidly eliminated its host. This study revealed the abundance and variety of phages infecting Gram-negative bacteria, particularly Enterobacteriaceae, in the commercial cucumber fermentation, suggesting that phages may play an important role in the elimination of Gram-negative bacteria, thereby facilitating the dominance of LAB and minimizing bloater defect. To our knowledge, this is the first report on the ecology of phages infecting Gram-negative bacteria in commercial cucumber fermentations.